2017
DOI: 10.1039/c7ra10634c
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed direct coupling of benzoxazin-2-ones with indoles for the synthesis of diverse 3-indolylbenzoxazin-2-ones: access to natural cephalandole A

Abstract: Diverse and functionalized 3-indolyl benzo[b][1,4]oxazin-2-ones were synthesized via copper-catalyzed direct coupling of benzo[b][1,4]oxazin-2-one and indoles in air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“… 9 Alternatively, a copper-catalyzed direct coupling of benzoxazin-2-ones with indoles was reported by Lee and coworkers. 10 Nevertheless, despite these advances, an efficient, green, and convenient protocol for the synthesis of these systems remains a topic of high interest in chemical research. 11 …”
Section: Introductionmentioning
confidence: 99%
“… 9 Alternatively, a copper-catalyzed direct coupling of benzoxazin-2-ones with indoles was reported by Lee and coworkers. 10 Nevertheless, despite these advances, an efficient, green, and convenient protocol for the synthesis of these systems remains a topic of high interest in chemical research. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies by other researchers revealed cross-coupling of two heteroarenes or heteroarenes with polyfluoroarenes in related copper-based manifold (Scheme ). …”
Section: Coppermentioning
confidence: 99%
“…[14] In 2017, Lee and co-workers have developed Cu-catalyzed oxidative CÀ H bond functionalization reaction of 1,4-benzoxazinone. [15] They reported a Cu-catalyzed direct crossdehydrogenative coupling reaction between benzoxazin-2-ones (1 j) and indoles (2 j). Initially, they tried reaction between benzoxazin-2-one and N-methylindole in the presence of 10 mol% CoCl 2 as catalyst in dichloroethane solvent at 60 °C under air for 24 hours, which gave only 32 % yield of the desired product (3 j).…”
Section: Cu-catalyzed Oxidative C(sp 2 )-H/c(sp 3 )-H Bond Functional...mentioning
confidence: 99%
“…In 2017, Lee and co‐workers have developed Cu‐catalyzed oxidative C−H bond functionalization reaction of 1,4‐benzoxazinone [15] . They reported a Cu‐catalyzed direct cross‐dehydrogenative coupling reaction between benzoxazin‐2‐ones ( 1 j ) and indoles ( 2 j ).…”
Section: Cu‐catalyzed Oxidative C(sp2)‐h/c(sp3)‐h Bond Functionalizat...mentioning
confidence: 99%